PENGARUH PENGATURAN POPULASI DAN UKURAN LEMPENGAN RUMPUT MANILA (Zoysia matrella (L.) Merr) TERHADAP PERTUMBUHAN DAN PERKEMBANGANNYA - Siti Nurisyah; Nurhajati Ansori Mattjik; Wiati Wulansari (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1994)
Zoysia matrella (L.) Merr. is a widely used ornamental grass, particularly in home and landscape gardens, because of its soft appearance and high quality. One of main problem is its low growth rate. Therefore, specific cultural techniques are required to accelerate its growth while maintaining its attractive appearance. This experiment was aimed to study the effect of sod size and planting distance of Zoysia mairella. on grass growth and development. The experiment was conducted at the IPB experimental station at Darmaga IV, Bogor, for 8 months and was completed in August 1990. The trials used a split plot design with 2 factors and 3 replications. Treatment consisted of 2 planting distances i.e. (20 x 20) cm and (25 x 25) cm, and 4 sod sizes, i.e. (2 x 2) cm, (5 x 5) cm, (8 x 8) cm, and (10 x 10) cm. The variables observed were percentage of coverage, rate of coverage, quality of leaf color quality of appearance, and uniformity of growth. The results indicated that population density did not significantly affect variables observed except for uniformity of growth. Hence, the larger the sod size, the higher its rate of coverage and the more uniform its appearance, but the lower its quality of appearance. Statistically, the sod size significantly affected the percentage of coverage, rate of coverage, quality of appearance, and uniformity of growth